2013
DOI: 10.1371/journal.pone.0070803
|View full text |Cite
|
Sign up to set email alerts
|

Stool Microbiome and Metabolome Differences between Colorectal Cancer Patients and Healthy Adults

Abstract: In this study we used stool profiling to identify intestinal bacteria and metabolites that are differentially represented in humans with colorectal cancer (CRC) compared to healthy controls to identify how microbial functions may influence CRC development. Stool samples were collected from healthy adults (n = 10) and colorectal cancer patients (n = 11) prior to colon resection surgery at the University of Colorado Health-Poudre Valley Hospital in Fort Collins, CO. The V4 region of the 16s rRNA gene was pyroseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
495
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 566 publications
(532 citation statements)
references
References 45 publications
33
495
1
3
Order By: Relevance
“…Akkermansia, a mucin-degrading bacterium in the phylum of Verrucomicrobia, has been reported to correlate with CRC in humans and in a mouse model 37,38 . We observed no difference in the abundance of Akkermansia among healthy controls, advanced adenoma and carcinoma samples (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia, a mucin-degrading bacterium in the phylum of Verrucomicrobia, has been reported to correlate with CRC in humans and in a mouse model 37,38 . We observed no difference in the abundance of Akkermansia among healthy controls, advanced adenoma and carcinoma samples (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why age or different antibiotic uptakes may not promote measurable metabolic differences in patients with pathogen-caused diarrhoea and that the differences within patients in each of the three Functional robustness associated with C. difficile D Rojo et al groups investigated were small regardless of patient characteristics and medical history. The effects of various pathophysiologies in the human gut metabolome have been previously examined (Saric et al, 2008;Le Gall et al, 2011;Marcobal et al, 2013;Weir et al, 2013;Bondia-Pons et al, 2014). However, no clear associations between faecal fluid metabolome patterns and individual pathophysiologies (for example, weight gain or the presence of a disease) have been previously observed; this was mainly due to large inter-individual variation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major differences between our study and previous studies examining total faecal material is that herein we focused on isolating metabolites from microbes isolated from stool material followed by metabolic profiling of gut microbiota rather than on examining total faecal fluids, which are known to contain a complex mixture of metabolites provided from the diet, the host and intestinal bacteria. Such complex mixtures are commonly investigated in metabolomics studies (Saric et al, 2008;Le Gall et al, 2011;Marcobal et al, 2013;Weir et al, 2013;Walker et al, 2014). Metabolites from intestinal bacteria (rather than dietary or host metabolites) are required to maintain and repair the large intestine and to support human health (Kibe et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Several studies have attempted to apply high-throughput sequencing followed by network correlation analysis to identify gut bacteria associated with colorectal tumors. [6][7][8][9][10][11] While each study concluded that CRC is associated with gut dysbiosis, a significant shift in the gut microbiome community structure relative to healthy control populations, there has been a lack of consistently observed dysbiotic microbiota patterns.…”
Section: Introductionmentioning
confidence: 99%